Production, Characterization And Identification Of Bioactive Peptides From Annona Squamosa L. Seeds - Sofian, Nurul Hidayatul Afifah Saufi (2017)
Annona squamosa L. seed protein isolate (ASPI) and defatted protein isolate (DASPI) were successfully isolated using phosphate buffer at pH 8 followed by acidic precipitation at pH 4.5. The predominant proteins found in the seeds were β-conglycinin and glycinin. The amino acid profiles showed that the protein isolates contained a high amount of glutamic acid, glycine, aspartic acid, and leucine with essential to total amino acid ratio of 0.4. The Fourier transform infrared (FTIR) spectra showed that the isolated proteins exhibited a similar functional group of protein, which was extracted from legumes, and the isoelectric point (pI) was found at pH 3-4. The functionalities of both protein isolates were also investigated. The bioactivities were evaluated based on 2,2-diphenyl-1-picrylhydrazyl scavenging activity (DPPH), ferric reducing antioxidant power (FRAP), α-amylase, ACE inhibitory and lipase inhibitory activity assays.